C3 liquid phase selective hydrogenation catalyst as well as preparation method and application thereof

By using a modified alumina support in the carbon three-liquid phase selection hydrogenation catalyst, the number and type of oxygen-containing groups on the surface of the support are increased, and the metal active components are uniformly distributed thereon, the problem of unstable catalyst performance is solved, and a high activity and selective catalyst preparation is achieved.

CN119680535AActive Publication Date: 2025-03-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311235647.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

During mass production of existing carbon three-liquid hydrogenation catalysts, due to the differences in the surface chemosorption properties of the alumina support, the catalyst performance is unstable and the activity and selectivity are insufficient.

Method used

Using a carrier containing alumina and carbides, the number and type of oxygen-containing groups are increased by surface treatment to prepare a modified alumina carrier with improved chemical adsorption properties and pore structure, and the metal active components are evenly distributed on its surface.

Benefits of technology

The performance stability and activity selectivity of the catalyst are improved, ensuring the consistency and efficiency of the catalyst performance in batch production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004467337080000121
    Figure BDA0004467337080000121
  • Figure BDA0004467337080000131
    Figure BDA0004467337080000131
  • Figure BDA0004467337080000132
    Figure BDA0004467337080000132
Patent Text Reader

Abstract

The invention provides a C3 liquid phase selective hydrogenation catalyst as well as a preparation method and application thereof. The catalyst provided by the invention comprises a modified alumina carrier and a Pd metal component loaded on the carrier, the modified alumina carrier is prepared from components containing alumina and inorganic carbon species through surface treatment means such as heat treatment, crystallization, oxidation and the like, and the surface of the modified alumina carrier is rich in oxygen-containing groups. The oxygen-containing groups on the carrier in the catalyst provided by the invention can promote uniform distribution of the metal active components on the surface of the carrier, and the catalytic activity and selectivity of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a C3 liquid phase selective hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] C3 liquid phase selective hydrogenation catalyst is used in steam cracking to produce ethylene and propylene. The separated C3 fraction usually contains 2 mol% to 6 mol% of propyne (MA) and propadiene (PD). Propylene contains trace amounts of propyne and propadiene, which will lead to a decrease in catalyst activity during propylene polymerization, increase the consumption of polypropylene catalyst, and also affect the performance of polypropylene products. In industry, the selective hydrogenation method is generally used to convert propyne and propadiene into propylene, which not only removes impurities but also increases propylene production.

[0003] C3 liquid phase selective hydrogenation catalyst generally uses palladium as the main active component, adds metal additives such as silver and copper, and uses alumina as a carrier. In order to improve the activity and selectivity of the C3 hydrogenation catalyst, the palladium loading method can be optimized, multi-component metal additives can be added, and the chemical adsorption performance and pore structure of the alumina carrier can be improved. Chinese patent CN101875009A uses ionizing radiation to form evenly distributed palladium particles on the surface of the alumina carrier, which improves the activity and reduces the palladium loading; Chinese patent CN107107049A changes the adsorption capacity of the palladium catalyst for reactants by adding organic phosphorus compounds, improves the activity and selectivity, and enhances the ability to resist poisons.

[0004] In the preparation process of C3 liquid phase hydrogenation catalyst, the alumina carrier not only plays the role of dispersing metal components, but also provides a place for the reaction to occur. The good pore structure can promote the diffusion of reactants and products. By optimizing the molding method of the alumina carrier, adding modification additives, and preparing composite carriers based on alumina, the surface chemical adsorption properties and physical pore structure of the alumina carrier can be improved, thereby improving the hydrogenation performance of the catalyst.

[0005] Chinese patent CN1958155A discloses a method of coating Al on an inert carrier of talcum powder, refractory clay or silicon carbide. 2 O 3 The coating uses Pd as the main active component and Ag, alkali metals, etc. as auxiliary active components in the alkyne selective hydrogenation catalyst. By controlling the thickness of the alumina coating, the distribution of the metal active components on the carrier surface can be promoted, thereby improving the hydrogenation performance.

[0006] Chinese patent CN1279126A discloses the use of diatomaceous earth, SiO 2 、TiO 2 、Al 2 O 3The catalyst composed of metal components such as Pd and Bi loaded with the like as carriers has high selectivity and high activity in the selective hydrogenation reaction, while reducing the amount of green oil generated and extending the catalyst life.

[0007] The existing C3 liquid phase selective hydrogenation catalyst and its preparation method are greatly affected by the performance of alumina carrier during mass production. The surface chemical adsorption properties of alumina carriers produced in different batches are different, which affects the performance of the prepared catalyst. Therefore, it is necessary to develop a C3 liquid phase selective hydrogenation catalyst with a simple preparation method, stable mass production performance, good activity and selectivity. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a C3 liquid phase selective hydrogenation catalyst and its preparation method and application. The present invention adopts a carrier comprising alumina and carbide, and the carrier contains a high content of oxygen-containing groups to prepare a catalyst with stable mass production performance, good activity and selectivity.

[0009] One of the purposes of the present invention is to provide a C3 liquid phase selective hydrogenation catalyst, comprising a modified alumina carrier and a Pd metal component loaded on the carrier, wherein the modified alumina carrier is a modified alumina carrier having a surface rich in oxygen-containing groups obtained by surface treatment of components including alumina and inorganic carbon species.

[0010] According to the present invention, the C3 liquid phase selective hydrogenation catalyst is:

[0011] The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; and / or,

[0012] In terms of mass percentage, the inorganic carbon species is 0.5 to 20% of the amount of alumina, preferably 2 to 15%;

[0013] The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; wherein the content of the carboxyl group in the modified alumina carrier is 1 to 80 mmol / g, preferably 1 to 60 mmol / g; the content of the carboxyl group is 1 to 80 mmol / g, preferably 1 to 60 mmol / g; the content of the lactone group is 1 to 60 mmol / g, preferably 3 to 40 mmol / g;

[0014] The specific surface area of ​​the modified alumina carrier is 10 to 180 m 2 / g, water absorption rate is 30-120%, strength is 30-150N / particle, bulk density is 0.4-1.0g / ml, pore volume is 0.3-1.2ml / g;

[0015] The modified alumina carrier further contains an inorganic compound other than alumina which is optionally added; preferably, the inorganic compound other than alumina is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide, and hydrotalcite, and the mass ratio of the inorganic compound other than alumina to alumina is (0-30):100, preferably (0-28):100;

[0016] Based on the total weight of the catalyst as 100%, the content of the Pd metal component is 0.08-0.8%, preferably 0.08-0.5%;

[0017] An auxiliary active metal component is optionally added to the catalyst. The auxiliary active metal component can be an auxiliary active metal commonly used in the art. Preferably, the auxiliary active metal component is selected from at least one of Ag, Cu, Au, As, Sn, Cr, and Pb. Based on the total weight of the catalyst as 100%, the content of the auxiliary active metal component is 0 to 1%, preferably 0.05 to 0.6%.

[0018] The surface of the aluminum oxide carrier provided by the present invention contains at least one oxygen-containing group selected from hydroxyl, carboxyl and lactone groups, and the density of the oxygen-containing groups is 0.15 to 5 mmol / m 2 . The catalyst provided by the present invention optimizes the types and quantities of oxygen-containing groups on the surface of the alumina carrier by means of heat treatment, crystallization, oxidation, etc., and adds a certain amount of carbon species during molding, promotes the uniform distribution of metal active components on the surface of the alumina carrier, and improves the activity and selectivity of the prepared catalyst. The content of Pd metal and co-active metal components in the catalyst can be tested by atomic absorption or ICP methods, and those skilled in the art can select a suitable test method according to the type and content of the metal.

[0019] A second object of the present invention is to provide a method for preparing the above-mentioned C3 liquid phase selective hydrogenation catalyst.

[0020] The preparation method of the catalyst includes two steps: preparation of a modified alumina carrier and loading of active metal components. The preparation of the modified alumina carrier includes kneading a shaped powder into a shape, performing surface treatment, and increasing the number of oxygen-containing groups on the surface. In the present invention, the modified alumina carrier and its preparation can refer to Patent ZL202311028071.8, and the relevant contents disclosed in the aforementioned document are introduced into the present invention as a reference; the loading of active metal components includes loading the Pd metal component and an optional auxiliary active metal component on an alumina-containing carrier, drying and then calcining at high temperature to obtain a C3 liquid phase selected hydrogenation catalyst, wherein the loading method can adopt the loading method commonly used in the art, and the metal components can be loaded on the carrier together, or different metal components can be loaded on the carrier in steps.

[0021] According to the present invention, the preparation method of the C3 liquid phase selective hydrogenation catalyst comprises: granulating and surface treating a raw material comprising alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and optional inorganic compounds other than alumina to obtain the modified alumina carrier, and then loading the Pd metal component and the optionally added auxiliary active metal component on the carrier to obtain the C3 liquid phase selective hydrogenation catalyst.

[0022] According to an embodiment of the present invention, the preparation method of the C3 liquid phase selective hydrogenation catalyst specifically comprises:

[0023] (1) mixing alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina to obtain a mixed dry material;

[0024] (2) adding an acidic solution, kneading and forming, and extruding and granulating;

[0025] (3) drying and surface treating the granulated material to obtain a carrier;

[0026] (4) A solution containing a Pd metal component precursor compound and an optionally added co-active metal component precursor compound is loaded on a carrier, and after drying and calcining, the C3 liquid phase selective hydrogenation catalyst is obtained.

[0027] According to the present invention, in the method for preparing the C3 liquid phase selective hydrogenation catalyst: the step (1):

[0028] The alumina powder can be any alumina-containing powder material in the prior art, for example, the alumina powder is selected from pseudo-boehmite powder, alumina trihydrate powder, fast-release alumina powder, γ-Al 2 O 3 At least one of the powders; the pseudo-boehmite powder can be a commonly used pseudo-boehmite, preferably, the specific surface area of ​​the pseudo-boehmite powder is 200 to 300m 2 / g, pore volume 0.5-1.2ml / g, bulk density 0.2-0.4g / ml; the alumina trihydrate powder can be selected from at least one of gibbsite, bayerite, and diaspore; the fast-dehydrating alumina powder is obtained by fast dehydration of aluminum hydroxide, wherein the mass content of Na and Fe is less than 0.1%; the γ-Al 2 O 3 The powder can be obtained by calcining common pseudo-boehmite powder at high temperature;

[0029] The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch; the amount of the molding agent is 0.1-15wt%, preferably 0.1-10wt% of the total weight of the mixed dry materials;

[0030] The pore-forming agent is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol, and sesbania powder; the amount of the pore-forming agent is 0.1-15wt% of the total weight of the mixed dry material, preferably 0.1-10wt%;

[0031] The inorganic compound other than alumina is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite; the inorganic compound can be added arbitrarily according to the needs of the carrier, and can be adjusted within a wide range according to the composition of the modified alumina carrier;

[0032] The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; the amount of the inorganic carbon species can be adjusted within a wide range according to the composition of the modified alumina carrier.

[0033] According to the present invention, in the step (2) of the method for preparing the C3 liquid phase selective hydrogenation catalyst:

[0034] The concentration of the acidic solution can be adjusted within a wide range. Preferably, the concentration of the acidic solution is 0.001 to 1 mol / L.

[0035] The solvent in the acidic solution is selected from water or a mixed solution of water and an organic solvent. Preferably, the organic solvent is selected from at least one of methanol, ethanol, and ethylene glycol. When the solvent in the acidic solution is a mixed solution of water and an organic solvent, the volume ratio of the organic solvent to water is (0.05-1.5):1.

[0036] The acidic compound in the acidic solution is selected from at least one of an organic acid and an inorganic acid, preferably at least one of acetic acid, maleic acid, malic acid, citric acid, oxalic acid, formic acid, tartaric acid, ascorbic acid, salicylic acid, succinic acid, nitric acid, sulfuric acid, hydrochloric acid, hypochlorous acid, and phosphoric acid;

[0037] In step (2), the technicians in this field can adjust the amount of acid in the acidic aqueous solution according to the required specific surface area, strength, bulk density and other data of the alumina carrier; the kneading molding and extrusion granulation steps, the kneading molding time, and the extrusion molding pressure are related to factors such as the size of the equipment used, the composition of the alumina powder, and the composition of the acid solution, and the technicians in this field can make specific determinations based on experience.

[0038] According to the present invention, in the step (3) of the method for preparing the C3 liquid phase selective hydrogenation catalyst:

[0039] The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment; preferably,

[0040] The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa;

[0041] The crystallization conditions are: temperature of 120-250° C., pressure of 0.2-15 MPa, time of 4-18 h, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine;

[0042] The oxidation conditions are as follows: the temperature is 30-110° C., the time is 0.2-10 h, the oxidant used for oxidation is at least one selected from nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L;

[0043] The alkalization conditions are as follows: the temperature is 30-110°C, the time is 0.2-10h, the alkaline compound used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline compound solution is 0.1-10 mol / L;

[0044] The conditions for the irradiation treatment are: the ray source is selected from gamma rays and / or microwaves, wherein the gamma ray irradiation dose rate is 2-90 kGy / min, and the irradiation time is 0.2-24 h; the microwave power is 50-1000 W, and the irradiation time is 0.5-60 min.

[0045] According to the present invention, in the method for preparing the C3 liquid phase selective hydrogenation catalyst:

[0046] When the inorganic carbon species is at least one of coke, activated carbon, carbon black, and glassy carbon, heat treatment is used, or surface treatment is performed by crystallization and oxidation;

[0047] When the inorganic carbon species is at least one of charcoal, bamboo charcoal, and coconut shell charcoal, heat treatment is used, or heat treatment and irradiation are used for surface treatment;

[0048] When the inorganic carbon species is at least one of graphene, graphyne and diamond, the surface treatment is carried out by crystallization and oxidation, or by heat treatment and alkalization, or by heat treatment, alkalization and irradiation.

[0049] According to the present invention, in the step (4) of the method for preparing the C3 liquid phase selective hydrogenation catalyst:

[0050] The Pd metal component precursor compound is selected from at least one of soluble palladium compounds, preferably at least one of palladium chloride, palladium nitrate, palladium acetate, and palladium sulfate;

[0051] The auxiliary active metal component precursor compound is selected from at least one of chlorides, nitrates, acetates, sulfates, oxides, and metal organic compounds of Ag, Cu, Au, As, Sn, Cr, and Pb, and is preferably selected from at least one of chlorides, nitrates, and acetates of Ag, Cu, Au, As, Sn, Cr, and Pb;

[0052] The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid, and alcohol, preferably water;

[0053] The metal concentration in the solution containing the metal compound can be adjusted within a wide range, for example, the total metal content in the solution is 0.01 to 500 mg / mL;

[0054] The drying process can adopt the drying process and drying conditions commonly used in the art. The drying process allows the solvent used for impregnation to fully volatilize. The time required for drying can be selected according to the amount of solvent used and the drying temperature. For example, the drying conditions are: the drying temperature is 40 to 190° C. and the drying time is 4 to 48 hours; preferably, the drying temperature is 50 to 140° C. and the drying time is 4 to 24 hours;

[0055] The calcination can adopt the calcination process and calcination conditions commonly used in the art. The calcination time varies according to the content of the metal active component. As the content of the metal active component increases, the calcination time can be appropriately increased. For example, the calcination conditions are: the calcination temperature is 300-700°C, and the calcination time is 2-24h.

[0056] The third object of the present invention is to provide an application of the above-mentioned C3 liquid phase selective hydrogenation catalyst or the C3 liquid phase selective hydrogenation catalyst obtained by the above-mentioned preparation method in the hydrogenation reaction of C3 fractions.

[0057] According to the present invention, in the application:

[0058] The C3 liquid phase selective hydrogenation catalyst is subjected to reduction treatment before use. Preferably, the gas used for reduction includes hydrogen and other gases, the other gas is nitrogen or methane, and the molar percentage of hydrogen in the gas is 10-90%; the reduction temperature is 90-350° C.; the reduction time is 2-24 hours;

[0059] In the C3 liquid phase fraction, the molar percentage of propyne and propadiene is 0.5-6%;

[0060] The conditions of the hydrogenation reaction are: reaction temperature is 25-70°C, reaction space velocity is 5-120h -1 .

[0061] The catalyst of the present invention uses heat treatment, crystallization, oxidation, irradiation treatment and other means in the process of preparing the carrier containing aluminum oxide, thereby increasing the number of oxygen-containing groups of the aluminum oxide carrier; and enriching the types and number of oxygen-containing groups of the carrier by introducing carbon species. Due to the increase of oxygen-containing groups on the surface of the aluminum oxide carrier, the distribution of metal active components is more uniform and the thickness is controllable, and the prepared catalyst has better activity and selectivity. At the same time, the aluminum oxide carrier is surface modified after molding, and the physical properties of different batches of carriers are more consistent, and the performance of the prepared catalyst is also more stable. DETAILED DESCRIPTION

[0062] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0063] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0064] Example 1

[0065] Carrier preparation: Take a specific surface area of ​​150.3m 2 100g pseudo-boehmite powder, 5g sesbania powder, 8g carboxymethyl cellulose and 4g bamboo charcoal with a pore volume of 0.75ml / g and a bulk density of 0.22g / ml are mixed evenly. 1.8g concentrated nitric acid is added to 150g deionized water to prepare a mixed solution. The mixed solution is added to the mixed powders, and then put into a kneader to fully knead, and then extruded and granulated to obtain cylindrical particles with a particle size of 2-4mm, dried at 80℃ for 8h, and then heat treated with air and water vapor (volume ratio 0.8:1) at 1200℃ and 0.1MPa for 24h to obtain an alumina carrier.

[0066] Active metal component loading method: Take 25 mL of 10 mg Pd / mL palladium nitrate solution, weigh 0.395 g silver nitrate and add it to the palladium nitrate solution, dilute it to 65 mL with deionized water, and impregnate it on 100 g of the alumina carrier prepared by the above method. The impregnated sample was dried at 120°C for 4 hours and calcined at 500°C for 4 hours to obtain catalyst S1, with a Pd loading of 0.25% and an Ag loading of 0.25% by mass.

[0067] Example 2

[0068] Preparation of carrier: Take 100g pseudo-boehmite powder (same as Example 1), 10g silicon oxide, 8g coconut shell carbon, 5g sesbania powder, 10g ethyl cellulose, and mix them evenly. Take 1.8g concentrated nitric acid and add it to 150g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm. Then heat treat them with air and water vapor (volume ratio 0.8:1) at 600℃ and 1.5MPa for 12h to obtain an alumina carrier.

[0069] Active metal component loading method: 18 mL of 10 mg Pd / mL palladium nitrate solution was taken, diluted to 58 mL with deionized water, impregnated onto 100 g of the alumina carrier prepared by the above method, dried at 110°C for 6 h, and calcined at 500°C for 8 h to obtain a Pd-containing catalyst precursor. 0.333 g of copper chloride was weighed, added to 58 ml of deionized water, and the Pd-containing catalyst precursor was impregnated with the prepared Cu solution, then dried at 110°C for 6 h, and calcined at 500°C for 8 h to obtain catalyst S2, with a Pd loading of 0.18% and a Cu loading of 0.15% by mass.

[0070] Example 3

[0071] Carrier preparation: Take a specific surface area of ​​200.3m 2 100g of alumina trihydrate powder with a pore volume of 1.42ml / g and a bulk density of 0.15g / ml, 5g of polyethylene glycol cellulose, 5g of polyvinyl alcohol, and 12g of graphyne are mixed evenly. Take 2.2g of concentrated sulfuric acid and add it to 125g of deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put it into a kneader and knead it thoroughly, then extrude and cut it into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry it at 80℃ for 8h, heat treat it at 300℃, 3MPa of carbon dioxide and nitrogen (volume ratio 0.5:1) for 1h, then soak it in 5mol / L potassium carbonate solution, soak it at 60℃ for 6h, and then irradiate it with 2kGy / min of gamma rays for 24h to obtain an alumina carrier.

[0072] Active metal component loading method: Take 30 mL of 10 mg Pd / mL palladium chloride solution, dilute it to 71 mL with deionized water, add 0.521 g of chloroauric acid, stir evenly and impregnate it on 100 g of alumina carrier prepared by the above method, dry it at 100°C for 12 h, and calcine it at 450°C for 12 h to obtain catalyst S3. By mass content, the Pd loading amount is 0.30%, and the Au loading amount is 0.25%.

[0073] Example 4

[0074] Preparation of carrier: Take 120g pseudo-boehmite powder (physical properties are the same as in Example 1), 20g γ-Al 2 O 3 Powder, 10g fast-dealumina powder, 4.5g sesbania powder, 5g starch, 3.7g carbon black, mix well. Weigh 2.5g concentrated hydrochloric acid and 1.2g acetic acid, add to 160g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry at 80℃ for 8h, crystallize at 120℃ and 0.2MPa for 18h, then soak in a mixed solution of 0.1mol / L nitric acid and 0.1mol / L hydrogen peroxide at 80℃ for 10h, freeze-dry at -40℃ for 8h to obtain an alumina carrier.

[0075] Active metal component loading method: Take 20 mL of 10 mg Pd / mL palladium nitrate solution, dilute it to 65 mL with deionized water, add 0.158 g of silver nitrate, stir evenly and impregnate it on 100 g of alumina carrier prepared by the above method, dry it at 140°C for 4 hours, and calcine it at 520°C for 4 hours to obtain a catalyst precursor containing Pd and Ag. Weigh 0.413 g of chromium nitrate, dissolve it in 65 ml of deionized water, impregnate the catalyst precursor containing Pd and Ag, then dry it at 120°C for 12 hours, and calcine it at 550°C for 6 hours to obtain catalyst S4, which has a Pd loading of 0.20%, an Ag loading of 0.10%, and a Cr loading of 0.05% by mass.

[0076] Example 5

[0077] Preparation of carrier: Take 120g pseudo-boehmite powder (physical properties are the same as in Example 1), 20g γ-Al 2 O 3Powder, 10g barium oxide, 5.8g cyanoethyl cellulose, 4.8g polypropylene glycol, 30g diamond, mix well. Weigh 6.9g ascorbic acid, 1.2g concentrated hydrochloric acid, add 175g ethanol and deionized water (volume ratio 5:1) solvent to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 100℃ for 4h, heat treat them at 350℃, 0.2MPa acetylene and argon (volume ratio 0.05:1) for 3h, then soak them in 0.1mol / L sodium hydroxide solution, soak them at 40℃ for 10h, and then irradiate them with 50W microwave for 60min to obtain an alumina carrier.

[0078] Active metal component loading method: Take 25 mL of 10 mg Pd / mL palladium chloride solution, dilute to 70 mL with deionized water, dry at 110°C for 12 hours, and calcine at 450°C for 8 hours to obtain a Pd-containing catalyst precursor. Weigh 0.189 g of lead acetate, add it to 70 ml of deionized water, soak the Pd-containing catalyst precursor, then dry at 100°C for 6 hours, and calcine at 450°C for 8 hours to obtain catalyst S5, with a Pd loading of 0.25% and a Pb loading of 0.10% by mass.

[0079] Comparative Example 1

[0080] Preparation of carrier: Take 100g pseudo-boehmite powder (physical properties are the same as those in Example 1), 5g sesbania powder, 8g carboxymethyl cellulose, and 4g bamboo charcoal, and mix them evenly. Take 1.8g concentrated nitric acid and add it to 150g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powders, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm. After drying and air heat treatment (operating temperature, pressure, and time are the same as those in Example 1), an alumina carrier is obtained.

[0081] Active metal component loading method: Take 35 mL of 10 mg Pd / mL palladium nitrate solution, dilute it to 65 mL with deionized water, dry it at 120°C for 12 h, and calcine it at 500°C for 8 h to obtain catalyst D1. The Pd loading amount is 0.35% by mass content.

[0082] Comparative Example 2

[0083] Preparation of carrier: Take 100g pseudo-boehmite powder (physical properties are the same as those in Example 1), 10g silicon oxide, 5g sesbania powder, and 10g ethyl cellulose, and mix them evenly. Then take 1.8g concentrated nitric acid and add it to 150g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powders, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm. After drying and air heat treatment (operating conditions are the same as those in Example 2), an alumina carrier is obtained.

[0084] The active metal component loading method was the same as that of Comparative Example 1 to obtain catalyst D2.

[0085] Comparative Example 3

[0086] Carrier preparation: Take a specific surface area of ​​160.4m 2 / g, pore volume 0.8ml / g, bulk density 0.16g / ml 20g alumina trihydrate powder, 80g α-Al 2 O 3 Powder, 6g polyethylene glycol, 7g methylcellulose, mixed evenly. Take 4g oxalic acid and 4g acetic acid, add 150g deionized water, prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut into pellets to obtain cylindrical particles with a particle size of 2-4mm, and after drying, crystallization and oxidation (operating conditions are the same as in Example 3), obtain an alumina carrier.

[0087] The active metal component loading method was the same as that of Comparative Example 1 to obtain catalyst D3.

[0088] Test Example 1 Carrier Characterization

[0089] Determination method of oxygen-containing groups on alumina carrier: The Boehm chemical method was used to determine the nature and quantity of oxygen-containing groups on the carrier. Three portions of 0.6 g of the carrier were weighed and placed in 40 ml of 0.05 mol / L NaHCO 3 、Na 2 CO 3 and NaOH solution for 24 hours. 10 ml of the soaking solution was titrated with 0.05 mol / L hydrochloric acid. Each sample was titrated three times, and the arithmetic mean was taken. The number of various oxygen-containing groups on the carrier was calculated based on the consumption of alkali, and the oxygen-containing group density was obtained in combination with the carrier specific surface data. The results are listed in Table 1.

[0090] Table 1. Test results of oxygen-containing groups on alumina carriers in Examples and Comparative Examples

[0091]

[0092] It can be seen from Table 1 that the content and density of oxygen-containing groups on the surface of the alumina support prepared by the method of the present invention are significantly higher than those of the alumina support of the comparative example. By adjusting the raw material ratio, preparation process parameters and conditions, the method of the present invention can achieve the regulation of the number and type of oxygen-containing groups on the surface of the alumina support.

[0093] Test Example 2 Catalyst Performance Evaluation

[0094] The above catalyst was used to carry out C3 liquid phase selective hydrogenation reaction, and the experimental conditions were as follows:

[0095] 50 ml of catalyst was loaded into a stainless steel tubular reactor. After nitrogen replacement, hydrogen was introduced to activate at 120°C for 4 hours. After cooling to room temperature, nitrogen was used to purge and replace, and liquid C3 reaction raw materials were introduced. The molar composition of the reaction materials was: 5.12% propane, 92.3% propylene, 1.19% propadiene, 1.39% propyne, the molar ratio of hydrogen to alkyne (propyne and propadiene) was 1.5, the reactor inlet temperature was 35°C, and the reaction pressure was 1.8 MPa. The conversion rate and selectivity of each catalyst were investigated under the same reaction conditions, and the reaction results are shown in Table 2.

[0096] The conversion (%) and selectivity (%) of propyne and propadiene (collectively referred to as MAPD in the table) are calculated as follows:

[0097]

[0098]

[0099] In the formula, MAPD stands for propyne and propadiene, (MAPD) in is the content of MAPD at the reactor inlet, (MAPD) out is the content of MAPD at the reactor outlet, (C 2 H 6 ) in The reactor inlet C 2 H 6 The content of (C 2 H 6 ) out The reactor outlet C 2 H 6 The content of each component is measured by a gas chromatograph equipped with a FID detector.

[0100] Table 2. Evaluation results of catalysts obtained in Examples and Comparative Examples

[0101] catalyst MAPD conversion rate (%) Selectivity (%) S1 97.1 83.4 S2 94.2 80.5 S3 99.5 81.3 S4 96.5 85.3 S5 98.3 83.2 D1 88.5 80.1 D2 87.2 81.2 D3 89.2 79.3

[0102] According to the evaluation reaction results in Table 2, the catalysts of Examples 1 to 5 are used for the liquid phase selective hydrogenation reaction of C3, and the conversion rate is significantly higher than that of Comparative Examples 1 to 3, and the selectivity is also higher at a higher MAPD (propyne and propadiene) conversion rate. It can be seen that the catalyst comprising alumina and carbide in the present invention has more excellent catalytic activity and selectivity.

Claims

1. A C3 liquid phase selective hydrogenation catalyst, comprising a modified alumina carrier and a Pd metal component loaded on the carrier, wherein the modified alumina carrier is a modified alumina carrier having a surface rich in oxygen-containing groups obtained by surface treatment of components including alumina and inorganic carbon species.

2. The catalyst according to claim 1, characterized in that The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; and / or, In terms of mass percentage, the inorganic carbon species is 0.5 to 20% of the amount of alumina; and / or, The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; and / or, The specific surface area of ​​the modified alumina carrier is 10 to 180 m 2 / g, water absorption of 30-120%, strength of 30-150N / particle, bulk density of 0.4-1.0g / ml, pore volume of 0.3-1.2ml / g; and / or, The modified alumina support further contains an inorganic compound other than alumina which is optionally added; and / or, Based on 100% of the total weight of the catalyst, the content of the Pd metal component is 0.08-0.8%; and / or, Optionally, an active metal component is added to the catalyst.

3. The catalyst according to claim 2, characterized in that In terms of mass percentage, the inorganic carbon species is 2 to 15% of the amount of alumina; and / or, The modified alumina carrier has a hydroxyl content of 3 to 60 mmol / g, preferably 5 to 40 mmol / g; and / or, In the modified alumina carrier, the content of carboxyl groups is 1 to 80 mmol / g, preferably 1 to 60 mmol / g; and / or, In the modified alumina carrier, the content of lactone groups is 1 to 60 mmol / g, preferably 3 to 40 mmol / g; and / or, The inorganic compound other than aluminum oxide is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite; and / or, In the modified alumina carrier, the mass ratio of the inorganic compound other than alumina to alumina is (0-30):100, preferably (0-28):100; and / or, Based on 100% of the total weight of the catalyst, the content of the Pd metal component is 0.08-0.5%; and / or, The auxiliary active metal component is selected from at least one of Ag, Cu, Au, As, Sn, Cr and Pb; and / or, Based on 100% of the total weight of the catalyst, the content of the active metal component is 0-1%, preferably 0.05-0.6%.

4. A method for preparing the C3 liquid phase selective hydrogenation catalyst according to any one of claims 1 to 3, comprising: The raw materials including alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and optional inorganic compounds other than alumina are granulated and surface-treated to obtain a modified alumina carrier, and then the Pd metal component and the optionally added auxiliary active metal component are loaded on the carrier to obtain the C3 liquid phase selective hydrogenation catalyst.

5. The preparation method according to claim 4, characterized in that: The preparation method specifically comprises: (1) mixing alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species, and an inorganic compound other than alumina that is optionally added to obtain a mixed dry material; (2) adding an acidic solution, kneading and forming, and extruding and granulating; (3) drying and surface treating the granulated material to obtain a modified alumina carrier; (4) A solution containing a Pd metal component precursor compound and an optionally added co-active metal component precursor compound is loaded on a carrier, and after drying and calcining, the C3 liquid phase selective hydrogenation catalyst is obtained.

6. The preparation method according to claim 5, characterized in that: In the step (1): The alumina powder is selected from at least one of pseudo-boehmite powder, alumina trihydrate powder, fast-release alumina powder, and γ-Al2O3 powder; and / or, The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch; and / or, The amount of the molding agent is 0.1-15wt%, preferably 0.1-10wt% of the total weight of the mixed dry materials; and / or, The pore-forming agent is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol and sesbania powder; and / or, The amount of the pore-forming agent is 0.1-15 wt %, preferably 0.1-10 wt % of the total weight of the mixed dry materials; and / or, The inorganic compound other than aluminum oxide is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite; and / or, The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne and diamond.

7. The preparation method according to claim 5, characterized in that: In the step (2): The concentration of the acidic solution is 0.001 to 1 mol / L; and / or, The solvent in the acidic solution is selected from water or a mixed solution of water and an organic solvent. Preferably, the organic solvent is selected from at least one of methanol, ethanol and ethylene glycol; and / or, when the solvent in the acidic solution is a mixed solution of water and an organic solvent, the volume ratio of the organic solvent to water is (0.05-1.5):1; and / or, The acidic compound in the acidic solution is selected from at least one of organic acids and inorganic acids, preferably at least one of acetic acid, maleic acid, malic acid, citric acid, oxalic acid, formic acid, tartaric acid, ascorbic acid, salicylic acid, succinic acid, nitric acid, sulfuric acid, hydrochloric acid, hypochlorous acid, and phosphoric acid.

8. The preparation method according to claim 5, characterized in that: In the step (3): The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment; preferably, The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; and / or, The crystallization conditions are: temperature of 120-250° C., pressure of 0.2-15 MPa, time of 4-18 h, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine; and / or, The oxidation conditions are: temperature of 30-110° C., time of 0.2-10 h, the oxidant used for oxidation is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L; and / or, The alkalization conditions are as follows: the temperature is 30-110° C., the time is 0.2-10 h, the alkaline compound used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline compound solution is 0.1-10 mol / L; and / or, The conditions for the irradiation treatment are: the ray source is selected from gamma rays and / or microwaves, wherein the gamma ray irradiation dose rate is 2-90 kGy / min, and the irradiation time is 0.2-24 h; the microwave power is 50-1000 W, and the irradiation time is 0.5-60 min.

9. The preparation method according to claim 8, characterized in that: When the inorganic carbon species is at least one of coke, activated carbon, carbon black, and glassy carbon, heat treatment is used, or surface treatment is performed by crystallization and oxidation; or, When the inorganic carbon species is at least one of charcoal, bamboo charcoal, and coconut shell charcoal, heat treatment is used, or heat treatment and irradiation are used for surface treatment; or, When the inorganic carbon species is at least one of graphene, graphyne and diamond, the surface treatment is carried out by crystallization and oxidation, or by heat treatment and alkalization, or by heat treatment, alkalization and irradiation.

10. The preparation method according to claim 5, characterized in that: In the step (4): The Pd metal component precursor compound is selected from at least one of soluble palladium compounds, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate; and / or, The auxiliary active metal component precursor compound is selected from at least one of chlorides, nitrates, acetates, sulfates, oxides, and metal organic compounds of Ag, Cu, Au, As, Sn, Cr, and Pb, preferably at least one of chlorides, nitrates, and acetates of Ag, Cu, Au, As, Sn, Cr, and Pb; and / or, The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohol, preferably water; and / or, The total metal content in the solution is 0.01 to 500 mg / mL; and / or, The drying conditions are: drying temperature of 40-190°C, drying time of 4-48h; preferably, drying temperature of 50-140°C, drying time of 4-24h; and / or, The calcination conditions are as follows: the calcination temperature is 300-700° C. and the calcination time is 2-24 hours.

11. Use of the C3 liquid phase selective hydrogenation catalyst as claimed in any one of claims 1 to 3 or the C3 liquid phase selective hydrogenation catalyst obtained by the preparation method as claimed in any one of claims 4 to 10 in the hydrogenation reaction of a C3 fraction.

12. The use according to claim 11, characterized in that: The C3 liquid phase selective hydrogenation catalyst is subjected to reduction treatment before use. Preferably, the gas used for reduction includes hydrogen and other gases, the other gas is nitrogen or methane, and the molar percentage of hydrogen in the gas is 10-90%; and / or, the reduction temperature is 90-350° C.; and / or, the reduction time is 2-24 hours; and / or, The molar percentage of propyne and propadiene in the C3 liquid fraction is 0.5-6%; and / or the conditions of the hydrogenation reaction are: the reaction temperature is 25-70° C., and / or the reaction space velocity is 5-120 h -1 .

Citation Information

Patent Citations

  • C3 fraction selective hydrogenation catalyst and preparation method thereof

    CN101875009A

  • Selective hydrogenation catalyst and methods of making and using same

    CN107107049A

  • Alumina carrier as well as preparation method and application thereof

    CN119500087A

  • Catalyst for selective hydrogenation of acetylene hydrocarbon

    CN1279126A

  • Selective hydrogenation catalyst of alkine and diolefin, preparation method and application

    CN1958155A